The concept, features and prospects for the metaverse construct development - A. S. Yukhno (Мир новой экономики)
The paper discusses formation features of the metaverse concept in terms of the active introduction of information and communication technologies (ICT) into the state governance and business. The work’ goal is to study the concept content, its structure and development prospects. The author used such general scientiﬁc research methods as content analysis, comparative and correlation analysis, grouping, synthesis, systematization. In order to reveal the concept content, the paper reﬂects various approaches to the deﬁnition of the term “metaverse”. The author proposes his understanding and analyzes the issues of transition to the Web3 era and its relationship with the metaverse in the digital transformation of society and economy. The research presents a vision of the major elements of the metaverse at the current time. Despite the emerging risks, it assumes the active use of ICT and trends towards decentralization of the economy will contribute to the further implementation of the metaverse concept in our daily life. A practical signiﬁcance of the research lies in the possibility of using its provisions in the compilation of strategies for the development of corporations and state institutions. As an inference, the study gives some recommendations to corporations on taking part in the creation and it makes development of virtual worlds and a conclusion about the prospects for the concept progress in the medium term.